Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1677/jme.0.0290239
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of endometrial genes Connexin26, Connexin43, C3 and clusterin to primary estrogen, selective estrogen receptor modulators, phyto- and xenoestrogens

Abstract: Phytohormones and chemical compounds revealing estrogenic effects are of increasing interest for their possible influence on the physiology of the reproductive tract. The gap junction connexin (Cx) genes Cx26 and Cx43, the plasma glycoprotein clusterin gene and the complement C3 gene are highly regulated by estrogen in rat endometrium. To test the value of these genes as markers for estrogenic responsiveness we analyzed the effects of estradiol, diethylstilbestrol, the selective estrogen receptor modulators (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 58 publications
2
22
1
Order By: Relevance
“…Lactoferrin (Ltf) and complement factor 3 (C3) are induced to a high degree in the uterus by estrogen and antagonized by P 4 (28,29). They are abundantly expressed in the luminal epithelium on day 1 of pregnancy under the influence of a preovulatory estrogen surge but are dramatically downregulated on day 4 by rising P 4 levels from newly formed corpora lutea (1, 2).…”
Section: Implantation Failure Occurs In Fkbp52 -/-Mice Irrespective Omentioning
confidence: 99%
“…Lactoferrin (Ltf) and complement factor 3 (C3) are induced to a high degree in the uterus by estrogen and antagonized by P 4 (28,29). They are abundantly expressed in the luminal epithelium on day 1 of pregnancy under the influence of a preovulatory estrogen surge but are dramatically downregulated on day 4 by rising P 4 levels from newly formed corpora lutea (1, 2).…”
Section: Implantation Failure Occurs In Fkbp52 -/-Mice Irrespective Omentioning
confidence: 99%
“…Thus, it is not unexpected that dietary phytoestrogens could play a role in the pathophysiology of an estrogen-dependent (37) condition such as endometriosis. At the level of the endometrium, phytoestrogens have been shown to potentially act as agonists in animal models (38)(39)(40)(41). However, human studies have suggested that the dosage and length of supplementation may be important to consider because isoflavone treatment for a period of 5 y was associated with endometrial hyperplasia (19), whereas shortterm treatments were not (19,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Kuivanen et al (1989) also identified two estrogen-responsive proteins of the rat uterus as structurally related to complement component C3 [33]. Heikaus et al (2002) pointed to the supporting effect of estrogens on endometrial C3 gene expression [34]. Farkas et al (2008) found that neuroendocrine neurons of the rodent hypothalamus had significantly elevated complement C5a receptor transcriptions after estrogenic pretreatment and hypothesized that the C5a receptors are involved in the estrogen-induced calcium response of the hypothalamus, which links immune and neuroendocrine functions [35].…”
Section: Discussionmentioning
confidence: 99%